FACTORS INFLUENCING POOR EXAMINATION PERFORMSNCE IN COMMERCIAL SUBJECTS IN SENIOR SECONDARY SCHOOLS - EKRAMUR RAHMAN (International Journal of Multidisciplinary Research and Studies, 2021)
In Tanzania, during the 1970s, a programme that emphasised vocationalization of the ordinary level secondary school curriculum was implemented. This was in accordance with the Arusha Declaration's Education for Self-reliance Policy that was implemented in 1967. When individuals completed their education at this level, the goal of the policy was to have them ready for the workforce so that they would be self- sufficient and able to start their own businesses (Nyerere, 1967). As a result of the Arusha Declaration, the Ministry of Education issued Circular No. 2 of 1972, which stipulated that secondary schools were required to provide students with the opportunity to study commercial topics, such as commerce and bookkeeping or accounts, which were considered to be among the more practical subjects (referred to as bias subjects). Another circular, known as National Education Circular No. 3 of 1974, was issued by the Ministry of Education in 1974. This circular provided greater elaboration on the disciplines that were considered to be practical (bias).